CURRENCY FLUCTUATIONS AND COMMODITY PRICES: DISCUSS THE RELATIONSHIP BETWEEN CURRENCY MOVEMENTS (ESPECIALLY THE US DOLLAR) AND COMMODITY PRICES - Yadav, Pooja; Giri, Jagat Narayan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Background: This study explored the relationship between currency fluctuations, particularly those of the US dollar, and commodity prices, focusing on crude oil, gold, wheat, and soybeans. The inverse correlation between the US dollar and commodity prices is widely accepted, but this study aimed to provide primary data analysis to quantify this relationship and assess the sensitivity of different commodities to currency movements. Methods: A prospective cohort study was conducted over a 12-month period, collecting real-time data on commodity prices and US dollar exchange rates. Fifty participants, including commodity traders and financial analysts, provided transaction data for analysis. Descriptive statistics, correlation analysis, and multiple regression were used to analyze the data. The sensitivity of commodities to changes in the US dollar was assessed, and volatility and risk mitigation strategies employed by traders were also examined. Results: The study found a strong inverse relationship between the US dollar and the prices of crude oil and gold, with correlation coefficients of -0.72 and -0.65, respectively. Regression analysis showed that US dollar fluctuations explained 52% of the variance in crude oil prices (P = 0.0001) and 47% of the variance in gold prices (P = 0.0003). Agricultural commodities such as wheat and soybeans had weaker correlations with the US dollar, showing coefficients of -0.42 and -0.35, respectively. Volatility analysis indicated that crude oil and gold were more susceptible to price fluctuations than agricultural commodities. Hedging strategies, including forward contracts and currency options, were used by 65% of traders to mitigate currency risks. Conclusion: The study confirmed a significant inverse relationship between US dollar fluctuations and commodity prices, with crude oil and gold being most sensitive to currency movements. Agricultural commodities were less affected by currency changes, with external factors such as supply-demand dynamics playing a larger role. The findings suggest that currency fluctuations remain a critical factor for commodity traders, who actively employ hedging strategies to mitigate risks.